Eventfulness in English Narrative Fiction: A Diachronic Perspective (ENTHYMEMA, 2025)
This article is a contribution to the currently expanding field of diachronic narratology, i.e. the research into possible historical and cultural changes in the practice of narration, more precisely the question of how far the various narratological categories (which as such can be considered to be universal) underlie changes in their practical application in different periods and cultures. This article focuses specifically on the narratological category of the event analyzing and comparing the practical realization of eventfulness in two periods within the history of English narrative fiction, on the one hand in the middle ages (1100-1500) and on the other in the 18th century. It can be shown that the emphasis on eventfulness in narratives varies significantly between these epochs and, also within the medieval epoch, among genres.
Keywords: Event; Narrative; Diachronic Narratology; Medieval English Literature; Early Modern English Literature; Romance; Novel; Tale